Evaluation of Unexplained Dyspnea in A Young Athletic Male with Pectus Excavatum - Tardie, Gregory B. (Asist Group, 2005)
Pectus excavatum (PE) is a relatively common congenital deformity of the anterior chest wall associated with reduced exercise capacity. Uncertainty exists over the nature of physiologic impairment in PE. Evidence suggests that myocardial compression exerted by the displaced sternum on the right heart chambers, disables the ability of the heart to augment stroke volume during exercise. This case study describes the evaluation of an athletic 20 year old Caucasian male, lifelong non-smoker, with severe pectus deformity and previous fixation procedure to repair a sternal fracture. The patient performed an incremental cycle ergometer exercise test to determine the etiology of his dyspnea with exertion. The patient demonstrated normal work output and normal aerobic capacity but displayed dynamic hyperinflation. Mechanical restriction of tidal volume expansion appeared to be the major contributors to exercise limitation. These results are compared and contrasted with similar cases reported in the literature.